AFRICAN UNION’S SHARED VALUES AND THE DILEMMA OF DEMOCRACY IN WEST AFRICA - BARILEDUM Kia; SUNNY OKORO ABEKI (International Studies Journal)
Recently some West African Countries had their democratic governance disrupted in the face of shared values developed and agreed as standard practice for member states of the African Union. Against this background, the paper examined the African Union Shared values and the dilemma of democracy in West Africa sub region. The paper adopted historical and descriptive research method and obtained data from secondary sources particularly Africa Union documents, Nigeria Institute of International Affairs, and other related scholarly journals. First, the study found that AU shared values were developed   in their desire of meeting the needs of Africans through the adoption of norms and principles that encourage collective actions and solutions to challenges facing the region of Africa. Second, the study discovered a huge gap in the declaration and policy commitment by leaders of some west African countries particularly Niger Republic, Mali, and others that recently experienced military takeover of governance to AU’s Shared values. The gap is primarily caused by autocratic tendencies and political corruption. Its further revealed that the AU is weak to enforces her declaration on democratic governance. If this done, Military intervention will be less likely. The study revealed these through critical analysis of the ingredients of African Union Shared values and its declaration on democratic governance. Based on the findings, the study recommends among others commitment of leaders of the sub region to good governance, justice, rule of law that ensure peace and sustainable development that are antidotes to military disruption of constitutional democratic governance. AU Members should unite in the implementation of its agreed shared values.